Parathyroid Adenoma Presenting with Recurrent Abdominal Pain and Renal Calculi - Gautam, Dipendra; Devkota, Ishwor Raj; Mainali, Sandesh; Chaudhari, Bijaya Kumar (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Introduction: Parathyroid adenoma is the single most common cause of hyperparathyroidism. Reported incidence of parathyroid adenoma varies widely and is 30- 90%. Approximately 80% to 85% of patients with primary hyperparathyroidism were found to have solitary parathyroid adenoma. The hyperparathyroidism due to parathyroid adenoma may progress insidiously over several years and eventually presents as renal colic or symptoms may manifest over a considerably shorter period of time. Greater than 50% of patients present with nephrolithiasis or nephrocalcinosis. The present case report describes a 48 year old male patient with symptoms of abdominal pain. Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015